Prevalence and predictive factors of Chlamydia trachomatis genital infection in inmates 25 to 65 years old in four Catalan prisons - D Carnicer-Pont; V González; E López-Corbeto; E Turu (Sociedad Española de Sanidad Penitenciaria, 2020)
ABSTRACT Objectives Determine the prevalence of Chlamydia trachomatis (CT) infection, the risk factors for infection in inmates aged 25 to 65 years old in four Catalan prisons. Materials and methods This is a cross sectional study conducted in four Catalan prisons chosen at convenience with a random stratified sample of the penitentiary population 25 to 65 years old taken within these centres. A urine specimen was analysed using the Anyplex CT/NG Seegene technique. An ad hoc questionnaire was used to determine sociodemographic and behavioural risk factors for infection within the previous year. The prevalence estimates of CT were calculated. Crude and adjusted odds ratios (ORs) and 95% Confidence Intervals (CIs) were used to estimate associations between infection and risk factor. Results Out of 1,469 participants, 15 men tested positive for CT (prevalence: 1.02%). We explored age, country of birth, education, occupation, sexual orientation, age initiation sexual activity, number and type of sexual partners (sporadic vs. stable) in a year, concurrency of sexual partners, preservative use in previous sexual relationship, etc. The only factor independently associated with infection was being heterosexual man having sexual relationships with different sporadic partners. Among those who had had an STI (Sexually Transmitted Infection) in life 27% did not notify to all their partners and the main reason was not being able to retrieve them. Conclusions CT prevalence in inmates 25 to 65 years old is very low in four prisons of Catalonia. No systematic screening of infection is justified although prisoners having different sporadic sexual partners may need more sexual infection prevention advice.